Contextualized learning in Medical Biochemistry: toward deeper understanding through mixed methods - Millán Hernández, Manuel; Albarrán-Pérez, Daniela Francelia (Spanish Journal of Medical Education, 2025)
This letter to the editor offers a critical reflection on the article “Impact of the implementation of clinical cases and experimental practices on the academic performance of second-semester students in Medical Biochemistry,” recently published in this journal. The study’s valuable contribution is acknowledged, particularly its rigorous quantitative approach and the implementation of active strategies that integrate biochemical theory with clinical reasoning. The significant improvement in academic performance and the methodological coherence of the intervention are highlighted as key strengths. However, the letter proposes extending the analysis through an explanatory sequential mixed-methods design, allowing for a deeper exploration of students’ perceptions and the underlying formative processes. Furthermore, the findings are contextualized within pedagogical models such as Team-Based Learning and the Master Adaptive Learner, in line with current trends in health professions education. The letter provides a constructive expert perspective rooted in mixed-methods research and basic sciences education.